Spring Barley Cost-Return Budget (W-B-F Rotation) in Western Kansas - Dumler, Troy J.; Thompson, Curtis R.; O'Brien, Daniel M. (My University, 2000)
This publications provides information on yield goals, variable and fixed costs, and profit and return factors for producing spring barley.
MF2097_2000_10
Keywords: MF2097; Crops; Economics; MF